Memcomputing with membrane memcapacitive systems. (12th May 2015) - Pershin, Y V; Traversa, F L; Ventra, M Di
Abstract: We show theoretically that networks of membrane memcapacitive systems—capacitors with memory made out of membrane materials—can be used to perform a complete set of logic gates in a massively parallel way by simply changing the external input amplitudes, but not the topology of the network. This polymorphism is an important characteristic of memcomputing (computing with memories) that closely reproduces one of the main features of the brain. A practical realization of these membrane memcapacitive systems, using, e.g., graphene or other 2D materials, would be a step forward towards a solid-state realization of memcomputing with passive devices.